Towards a global land surface climate fiducial reference measurements network. (1st March 2018) - Thorne, P. W.; Diamond, H. J.; Goodison, B.; Harrigan, S.; Hausfather, Z.; Ingleby, N. B.; Jones, P. D.; Lawrimore, J. H.; Lister, D. H.; Merlone, A.; Oakley, T.; Palecki, M.; et al.
Abstract : Instigating and maintaining a reference network for climate would aid future generations in understanding climate change. Such measurements require strict adherence to metrological best practices and sustained support. This article explores what would be required to make such a network work. Figure is the schematic of the instrumentation at a typical USCRN station in the CONUS. The triplicate configuration of temperature sensors is repeated in the three precipitation gauge weighing mechanisms and in the three sets of soil probes located around each tower. Abstract : There is overwhelming evidence that the climate system has warmed since the instigation of instrumental meteorological observations. The Fifth Assessment Report of the Intergovernmental Panel on Climate Change concluded that the evidence for warming was unequivocal. However, owing to imperfect measurements and ubiquitous changes in measurement networks and techniques, there remain uncertainties in many of the details of these historical changes. These uncertainties do not call into question the trend or overall magnitude of the changes in the global climate system. Rather, they act to make the picture less clear than it could be, particularly at the local scale where many decisions regarding adaptation choices will be required, both now and in the future. A set of high‐quality long‐term fiducial reference measurements of essential climate variables will enable future generations to make rigorous assessments of future climate change and variability, providing society with the best possible information to support future decisions. Here we propose that by implementing and maintaining a suitably stable and metrologically well‐characterized global land surface climate fiducial reference measurements network, the present‐day scientific community can bequeath to future generations a better set of observations. This will aid future adaptation decisions and help us to monitor and quantify the effectiveness of internationally agreed mitigation steps. This article provides the background, rationale, metrological principles, and practical considerations regarding what would be involved in such a network, and outlines the benefits which may accrue. The challenge, of course, is how to convert such a vision to a long‐term sustainable capability providing the necessary well‐characterized measurement series to the benefit of global science and future generations.